Breeding Management Practices of Jaffarabadi Buffalo in Junagadh District of Gujarat, India (Indian Journal of Animal Production and Management, 2024)
A field study was conducted in Junagadh  district of Gujarat to ascertain the breeding  management practices followed by Jaffarabadi  buffalo owners and data were collected from  randomly selected 320 respondents through  personal interview with the help of structured  interview schedule. The present study revealed that  all the respondents detected heat in their buffaloes  by behavioral signs. Majority (55.62%) of the buffalo  owners observed mucus discharge as the  symptoms of oestrus and bred their buffaloes by  artificial insemination (65.62%) between 12-18  hours after heat detection (77.19%). Majority  (73.12%) of respondents bred their buffaloes after  3 to 5 months of calving and only 20.93 percent  respondents followed the pregnancy diagnosis  during the three months of pregnancy. About 97.50  and 96.88 percent of the respondents treated their  buffaloes for anestrous/repeaters and  ROP/Prolapse, respectively. About 32.81 percent of  the respondents kept the breeding records of the  buffaloes. Majority (75.62%) of respondents  preferred pure breeding of their Jaffarabadi  buffaloes.
Keywords: breeding management; Jaffarabadi buffalo; Gujarat